MARUNDA AIR QUALITY INDEX BASED ON CONTENT OF PM 2.5 AND PM 10 ACCORDING TO THE CRITERIA DETERMINED BY ENVIRONMENTAL PROTECTION AGENCY OF UNITED STATE OF AMERICA - Yudhiyono Yudhiyono; Jaya Alamsyah; Mohamad Nurdin (Meteor STIP Marunda, 2023)
Marunda is an area located in North Jakarta, several Industrial and warehousing located in this area, as well as special port such as: Millitary port, coal and sand loading and unloading. As a Industrial and warehousing area, tranportation marunda dominated by Container Truck and heavy Equipment. Main source of energy for industrial area came from coal and petroleum, and main source of energy for transportation activity came from petroleum, this is the main cause of air pollution in Marunda. Indication of high levels of air pollution can be seen by amount of dust (fine particles) that scattered on the floor. Based on existing studies has been known that air pollution has negative impact for human health. In this articles will be discussed level of air pollution in marunda based on the content of particulate matter 2.5, particulate matter 10 and Nitrogen Dioxide in the air.